2009
DOI: 10.1002/chem.200802172
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Phosphonate‐Linked Aminoglycoside–Coenzyme A Bisubstrate and Use in Mechanistic Studies of an Enzyme Involved in Aminoglycoside Resistance

Abstract: Aminoglycoside N-6′-acetyltransferases (AAC(6′)s) are important determinants of antibiotic resistance. A good mechanistic understanding of these enzymes is essential to overcome aminoglycoside resistance. We have previously reported the synthesis of amide-linked and sulfonamide-linked aminoglycoside-coenzyme A conjugates which were useful mechanistic and structural probes of AAC(6′)s. We report here the synthesis of a phosphonate-linked aminoglycoside-coenzyme A variant, which is expected to be a superior mimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 40 publications
1
22
0
4
Order By: Relevance
“…115 A similar trend was observed for phosphonate-linked AGs and the decreased inhibitory potency was explained by proximity catalysis by enzymes. 116 AG-CoA bisubstrates are highly potent AAC(6′) inhibitors, however their inability to penetrate cells preclude in vivo studies.…”
Section: Aminoglycosides As Antibacterial Agentsmentioning
confidence: 99%
“…115 A similar trend was observed for phosphonate-linked AGs and the decreased inhibitory potency was explained by proximity catalysis by enzymes. 116 AG-CoA bisubstrates are highly potent AAC(6′) inhibitors, however their inability to penetrate cells preclude in vivo studies.…”
Section: Aminoglycosides As Antibacterial Agentsmentioning
confidence: 99%
“…[22] Since we envisioned ethynylphosphonamidates to be more reactive,wecarried out model reactions with the N-phenyl derivative 1 and glutathione under varying pH conditions and monitored the progress by UPLC-UV.I tw as observed that the conversion rate increases from pH 7.4 to 9.0 with only aslight increase from pH 8.5 to 9.0 ( Figure S2 in the Supporting Information). [22] Since we envisioned ethynylphosphonamidates to be more reactive,wecarried out model reactions with the N-phenyl derivative 1 and glutathione under varying pH conditions and monitored the progress by UPLC-UV.I tw as observed that the conversion rate increases from pH 7.4 to 9.0 with only aslight increase from pH 8.5 to 9.0 ( Figure S2 in the Supporting Information).…”
mentioning
confidence: 99%
“…[22] Basierend auf der Überlegung,d ass Ethinylphosphonamidate reaktiver sein kçnnten, haben wir Modelreaktionen zwischen dem N-Phenyl-Derivat 1 und Glutathion bei verschiedenen pH-Werten durchgeführt und den Verlauf der Reaktion mithilfe von UPLC-UV verfolgt. [22] Basierend auf der Überlegung,d ass Ethinylphosphonamidate reaktiver sein kçnnten, haben wir Modelreaktionen zwischen dem N-Phenyl-Derivat 1 und Glutathion bei verschiedenen pH-Werten durchgeführt und den Verlauf der Reaktion mithilfe von UPLC-UV verfolgt.…”
unclassified